Kreativitas Eka Rosy dalam Penciptaan Karya Tari Jejak - Fuadah, Eka Rosydatul; Rokhim, Nur (Institut Seni Indoensia Surakarta, 2023)
The Jejak dance work is a new choreography that has a background from the spirit of the Jathil Ponorogo dance. The value contained in the Jejak dance work is the value of the spirit of never giving up. The Jejak dance work is presented in the form of a group dance danced by six female dancers. This dance work isdivided into four parts, namely the intro, the first scene shows anxiety about goals and what you want to achieve, the second scene is conflict within the personal sphere, the third scene is self-confidence, which shows an atmosphere of enthusiasm or fighting spirit values. This study used a qualitative research method with a choreographic approach, to dissect the form of the choreography of the Jejak danceusing Y. Sumandiyo Hadi's theory. Meanwhile, to describe the creative process of creating Jejak dance works, it uses the theory of Rhodes, 4P (person, press, process, product). The stages in the process of creating a Jejak dance work go through several stages, namely the stage of determining ideas which are refined through several phases including the phase of selecting themes, maturation ofconcepts, observation, then the process of exploration, improvisation, and composition.This is very fundamental to creating a work that can be accounted for scientificallyacademically. The results of this research show: Eka Rosy's creativity in creating Jejak dance works is influenced by several factors (internal and external), Eka Rosy's creativity is reflected in Eka Rosy's ability to actualize ideas that are compiled through a process of exploration, improvisation, and composition then implemented in the form of works Jejak dance.Keywords: Jejak, dance work, creation process, choreography.